Bioinspired glycosaminoglycan hydrogels via click chemistry for 3D dynamic cell encapsulation. Issue 5 (1st November 2018) - Kuang, Liangju; Damayanti, Nur P.; Jiang, Chunhui; Fei, Xing; Liu, Wenjie; Narayanan, Naagarajan; Irudayaraj, Joseph; Campanella, Osvaldo; Deng, Meng
ABSTRACT: Cell encapsulation within 3D hydrogels is an attractive approach to develop effective cell‐based therapies. However, little is known about how cells respond to the dynamic microenvironment resulting from hydrogel gelation‐based cell encapsulation. Here, a tunable biomimetic hydrogel system that possesses alterable gelation kinetics and biologically relevant matrix stiffness is developed to study 3D dynamic cellular responses during encapsulation. Hydrogels are synthesized by crosslinking thiolated hyaluronic acid and thiolated chondroitin sulfate with poly(ethylene glycol) diacrylate under cell‐compatible conditions. Hydrogel properties are tailored by altering thiol substitution degrees of glycosaminoglycans or molecular weights of crosslinkers. Encapsulation of human mesenchymal stem cells through hydrogel gelation reveals high cell viability as well as a three‐stage gelation‐dependent cellular response in real‐time focal adhesion kinase (FAK) phosphorylation in live single cells. Furthermore, stiffer hydrogels result in higher equilibrium FAK activity and enhanced actin protrusions. Our results demonstrate the promise of hydrogel‐mediated cellular responses during cell encapsulation. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47212. Abstract : A new biomimetic hydrogel composed of hyaluronic acid, chondroitin sulfate, and poly(ethylene glycol) is developed through thiol‐Michael addition for 3D dynamic cell encapsulation. The hydrogel possesses tunable gelation kinetics and biologically relevant stiffness. Encapsulated mesenchymal stem cells show three‐stage gelation‐dependent responses as cell microenvironment evolves from precursor fluids to polymeric networks. Stiffer hydrogels promote higher focal adhesion kinase phosphorylation and enhanced actin protrusions.